Nivolumab-DTPA-Based PD-1 Imaging Reveals Structural and Pathological Changes in Colorectal Carcinoma - Li, Danni; Li, Xiao; Yang, Jian; Shi, Zhang; Zhang, Lu; Li, Rou; Peng, Ye; Liu, Jiajun; Zuo, Changjing (Frontiers in Bioengineering and Biotechnology, 2022)
Programmed cell death protein 1 (PD-1) expression is considered a prognostic marker of tumor response to the immuno-blocking therapy. In this study, nivolumab was conjugated with diethylenetriamine pentaacetate (DTPA) via condensation reaction between amidogen and p-SCN-Bn-DTPA, which provided labeling sites for 99mTc4+ or Gd3+ ions. SPECT and magnetic resonance T1 weighted imaging (T1WI) analyses were performed on mouse models of colorectal carcinoma expressing humanized PD-1 antigen. Furthermore, PD-1 expression in intestinal tracks was assessed by immunohistochemistry, and then compared with the imageological findings. Nivolumab-DTPA was synthesized with varying molar ratios and was labeled with Gd or 99mTc with a chemical purity of 96.28 ± 1.16% and good stability. In SPECT images, lesions with high 99mTc-DTPA-nivolumab uptake and relatively clear background were shown at 6 h. Thereafter, the suspected intestinal thickening in Gd-free T1WI was observed at 2 h after the addition of Gd-DTPA-nivolumab. Notably, the results of both SPECT and T1WI analyses were consistent with the postmortem examination and immunohistochemistry results (for linear correlation with target to non-target ratios, R2 = 0.8038, P < 0.05). In conclusion, nivolumab-DTPA could act as a probe precursor for identifying PD-1-positive lesions, not only through integrating the advantages of immunohistochemistry and molecular imaging but also by providing a noninvasive method for monitoring systemic changes.